The Role of Mining Materials in Group C Against Community Welfare In Ngawi Regency - Ivan Ardianto; Vincent Hadiwiyono; Tri Mulyaningsih (Universitas Muhammadiyah Ponorogo, 2018)
Natural resources in the mining sector are one of the natural resources in Indonesia. The sector produces various types of mining commodities that have different economic values. Ngawi Regency is one of the regions in East Java Province which has potential in the mining sector. One of the potential of the mine is group C excavation material. Since the construction of toll roads in the Ngawi Regency area, demand for mining products in the form of class C excavation materials as materials for toll road construction has increased rapidly. This has encouraged the growth of mining businesses in the region. Mining activities or businesses in addition to having a positive impact, such as the absorption of labor, also cause various negative impacts that affect the welfare of the community. Employment in the mining sector is indeed wide open which then causes people to switch from various sectors of employment to employment in the mining sector. The shift of employment to the mining sector has an impact on rising levels of income. However, this does not significantly affect the level of community welfare.